Advancing Interorganizational Crime and Violence Reduction Goals Through a Relational Change Intervention - Gebo, Erika (Criminal justice policy review, 2022)
Effective interorganizational collaboration is deemed essential to comprehensive crime and violence initiatives but rarely is it empirically assessed. An 18-month intervention to improve collaboration Comprehensive Gang Model (CGM) locations was used in this study to examine the impact on increasing community capacity to address gangs and violence and reducing gang and violence in the community. Relational coordination theory grounded the collaboration intervention. Results from the quasi-experimental design showed significant, increased collaboration and reduction in violent crime in one intervention site. Other crime reduction efforts were explored as counterfactuals. Matched comparison sites saw no change in the ability to work together or violence reduction. Study implications are that relational coordination interventions may facilitate the goal of working better together, but parallel evaluations for each of the five core CGM strategies are needed to understand the independent effects of each strategy on gang and violence reduction goals.